Psychological experiences of gratitude among dual role, lower middle income mothers in Sukoharjo: A phenomenological study - Afifah Nur Hasanah; Azzah Nilawaty (Universitas Ahmad Dahlan, 2026)
This study explores the essence of gratitude as a psychospiritual coping mechanism among dual-role mothers working in labor-intensive industrial sectors. A key gap in the existing literature lies in the dominance of Western positive psychology perspectives, which tend to be secular and individualistic, thereby overlooking the transcendental dimension in coping processes. Furthermore, there is a scarcity of studies that specifically position gratitude as a coping system for working mothers with dual burdens in religious contexts within the Global South. Employing a Husserlian descriptive phenomenological design, data were collected through in-depth interviews with three working mothers in Sukoharjo Regency. The findings reveal that gratitude functions as a dynamic and integrated coping system through three primary dimensions: (1) syukr qalbi as an emotional shield through acceptance of divine decree (qana’ah); (2) syukr amali, which sacralizes work-related burdens as acts of worship; and (3) syukr lisani as a form of verbal emotion regulation. Theoretically, this study contributes to Islamic psychology by integrating Al-Ghazali’s concept of gratitude into contemporary coping theory through a transcendental meaning-making mechanism. Practically and academically, these findings provide a foundation for developing culturally grounded mental health interventions and offer a novel perspective for cross-cultural psychology on how spiritual values can mitigate the impact of role conflict amid economic challenges.